I-Witness the best of Kara David (GMA Network, 2007)
"Buto't Balat" - Heartbreaking tales of malnourished children show us why Philippines could be the new Africa. "Uuwi Na Si Udong" - Boys work in sugarcane fields an ocean away from home to pay for their families' piling debts. Finalist 2007 New York Festivals. "Mga Anghel Sa Dapithapon" - Rachel is 9 and Maureen is 14, but already, their bodies are the physical age of their grandmothers. "Sa Mata Ni Ekang" - With a thief for a father, a drug dealer for a mother, and a pimp for a grandmother, how will the world look like in the eyes of four-year old? Silver Screen Award, 2007 US International Film and Video Festival. "Gamu-gamo Sa Dilim" - Schoolchildren struggle to give light to their future despite the darkness that surrounds them. Finalist for Best Public Affairs Program, 2002 Catholic Mass Media Awards. Best Aired Featured Story on Youth and Education, 2003 La Sallian Scholarum Awards.